A Secure and Scalable Data Sharing using Key Aggregate Crypto System - Patil, Bharati A (International Journal of Computer Sciences and Engineering, 2025)
Today, gaining popularity privacy for accessing outsourcing data stored on cloud is a major issue in cloud computing. In cloud storage data is stored on single physical machine and this stored data may shared by multiple users from different machines. User doesn't have control on accessing outsourced data. For identification of leaked data to everyone data access security or privacy for data is a challenging section. To store as well for sharing data securely Cryptosystem is used. In cryptosystem before storing data on cloud user firstly encrypt data then placed it on cloud. And then data decryption is performed when user want to access it. This task may require multiple keys for data encryption as well as data decryption. In proposed system key-aggregation is implemented on concept on merging or aggregating the encryption and decryption key into single one in cryptosystem for sharing of scalable data. It is very compressed formed of aggregation of key. In proposed approach unique key can hold multiple keys that are required. In proposed system concentrate on sharing data securely, efficiently among multiple users. Sharing data and delegation of data is possible as fixed sized of data blocks are created. In this proposed system implements Shamir secret sharing algorithm for securely, sharing aggregate key for multiple users.